Solvability of a System of Polynomial Equations Modulo Primes - Järviniemi Olli (CAMBRIDGE UNIV PRESS, 2025)
Let F be a system of polynomial equations in one or more variables with integer coefficients. We show that there exists a univariate polynomial D is an element of Z[x] such that F is solvable modulo p if and only if the equation D(x) 0 (mod p) has a solution.